Efeitos do resveratrol sobre células progenitoras neurais oriundas de embriões de camundongos infectados com Trypanosoma cruzi - Fracasso, Mateus (2018)
This study aimed to investigate the effect of resveratrol on the proliferation/self-renewal, migration, and neurogenesis of neural progenitor cells (NPCs) in embryos of mice experimentally infected by Trypanosoma cruzi. For the in vitro experimental protocol, females were divided into two groups: A (uninfected and pregnant), B (infected byT. cruzi and pregnant). The infection was performed 7 days after mating by the subcutaneous route with T. cruzi strains. Blood smear showed that infected females had trypomastigote forms of T. cruzi in the blood 5 days post infection, remaining parasitemia until samples were collected. Completed thirteen days of gestation was performed anesthesia of the females, and the removal of the embryos. The embryonic telencephalon was collected and cultured in cell culture. In the cultures, the effect of resveratrol at a concentration of 10 μM on nerve cell growth was tested. To verify the growth of NPCs, cell division was analyzed by the propidium iodide assay. The results revealed that T. cruzi infection decreases the size of uninfected compared neurospheres. Analysis by flow cytometry showed stimulation of neurogogenesis in infected NPCs. Treatment with resveratrol was able to increase the size of the neurospheres, although it failed to avoid the size changes of the neurospheres of infected embryos. Resveratrol also had no effects on the cell cycle, that is, we did not find any difference between groups for the phases of the cell cycle (S, G0/G1 and G2). Therefore, we conclude that Chagas disease is capable of affecting mature and immature neurons, as well as concluding that RSV treatment improves glycogenesis and restores neural migration during infection.